On the validity of the general order kinetics for analizing phosphorescence curves - Ortega, Federico Martin (2013)
The parameters characterizing trap and recombination centers, such as activation energies, recombination and trap probabilities, involved in thermoluminescent materials can be found by analyzing phosphorescence curves with an adopted model consisting of trap and recombination centers, and assuming the mechanisms involved in the carrier traffic (kinetics). Nowadays the most employed kinetics is the General Order kinetics (GO). Since this model is heuristic, this article reports how successful it is in providing reliable values for the traps parameters. The equations describing the traffic of carriers were used to generate simulated phosphorescence curves for specific values of trap and recombination parameters. These simulated phosphorescence curves were later analyzed with the GO kinetics, and the resulting parameters compared to the correct ones in order to evaluate the validity of the model.